2021
DOI: 10.1038/s41598-021-01899-8
|View full text |Cite
|
Sign up to set email alerts
|

TheraPearl Eye Mask and Blephasteam for the treatment of meibomian gland dysfunction: a randomized, comparative clinical trial

Abstract: Meibomian gland dysfunction (MGD) is the most common cause of dry eye disease (DED). In this study, we aimed to compare the effects of eyelid warming treatment using either TheraPearl Eye Mask (Bausch & Lomb Inc., New York, USA) or Blephasteam (Spectrum Thea Pharmaceuticals LTD, Macclesfield, UK) in a Norwegian population with mild to moderate MGD-related DED. An open label, randomized comparative trial with seventy patients (49 females, 21 males; mean age 53.6 years). Patients were randomly assigned to tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 61 publications
(84 reference statements)
0
13
0
Order By: Relevance
“…Multiple eyelid-warming devices, ie, a steam-based system goggle: Blephasteam ® (Spectrum Thea Pharmaceuticals LTD, Macclesfield, UK), heat-generating chemicals system eyemask: EyeGiene ® (Eyedetec Medical Inc., Danville, CA, USA), or gel-bead heat delivery system eyemask: TheraPearl ® (Bausch & Lomb Inc., New York, USA) might facilitate eyelid warming process and keep more consistent delivery of heat over the time when applying these devices on eyelid. 36 , 37 One previous research demonstrated the favorable effect of Blephasteam over the conventional method in terms of the better improvement of symptoms. 37 Future studies are required to identify the best ways to perform lid hygiene to optimize patient compliance and treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple eyelid-warming devices, ie, a steam-based system goggle: Blephasteam ® (Spectrum Thea Pharmaceuticals LTD, Macclesfield, UK), heat-generating chemicals system eyemask: EyeGiene ® (Eyedetec Medical Inc., Danville, CA, USA), or gel-bead heat delivery system eyemask: TheraPearl ® (Bausch & Lomb Inc., New York, USA) might facilitate eyelid warming process and keep more consistent delivery of heat over the time when applying these devices on eyelid. 36 , 37 One previous research demonstrated the favorable effect of Blephasteam over the conventional method in terms of the better improvement of symptoms. 37 Future studies are required to identify the best ways to perform lid hygiene to optimize patient compliance and treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…TheraPearl Eye Mask and Blephasteam for the treatment of meibomian gland dysfunction: a randomized, comparative clinical trial. 25 70 Improved symptoms Improved tear stability Not reported MGDRx OPTASE Murphy et al 2020. The Efficacy of Warm Compresses in the Treatment of Meibomian Gland Dysfunction and Demodex Folliculorum Blepharitis.…”
Section: Methodsmentioning
confidence: 99%
“…The study was part of an open-label, randomized comparative trial [ 8 ] (Clinicaltrials.gov ID: NCT03318874 ). The trial compared eyelid warming with either Therapearl eye mask (Bausch and Lomb Inc., New York, USA) or Blephasteam (Spectrum Thea Pharmaceuticals LTD, Macclesfield, UK) for the treatment of MGD.…”
Section: Methodsmentioning
confidence: 99%
“…The participants were randomized into treatment with either Blephasteam or Therapearl [ 8 ]. They were examined at the start of treatment (baseline), and after three and six months.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation